ECONOMICS OF BANKING - Cao, Jin. ([S.l.] : ROUTLEDGE, 2021)
The Economics of Banking provides an accessible overview of banking theory and practice. It introduces readers to the building blocks of fundamental theories and provides guidance on state-of-the-art research, reflecting the dramatic changes in the banking industry and banking research over the past two decades. This textbook explores market failure and financial frictions that motivate the role of financial intermediaries, explains the microeconomic incentives and behavior of participants in banking, examines microlevel market stress caused by economic recessions and financial crises, and looks at the role of monetary authorities and banking regulators to reduce systemic fragility as well as to improve macroeconomic stability. It delivers broad coverage of both the micro and macroeconomics of banking, central banking and banking regulation, striking a fine balance between rigorous theoretical foundations, sound empirical evidence for banking theories at work, and practical knowledge for banking and policymaking in the real world. The Economics of Banking is suitable for advanced undergraduate, master's, or early PhD students of economics and finance, and will also be valuable reading for bankers and banking regulators.
OCLC-licensed vendor bibliographic record.
Keywords: Banks and banking; BUSINESS & ECONOMICS / Banks & Banking; BUSINESS & ECONOMICS / Investments & Securities